Olivia becomes a vet - Harvey, Alex (Ready-to-read. Starting to read., 2011)
When Julian's pet lizard isn't feeling well and needs to visit the vet, Olivia takes her "way with animals" to the next level and imagines what it would be like to become a veterinarian.